Rethinking Deficit Discourses in Education Through Rural Education Research and the Concept of Querencia - Gouwens, Judith A.; Henderson, Robyn (Australian and International Journal of Rural Education, 2021)
This paper uses data from research projects that deliberately set out to tell positive stories about educators who were working with the children and families of migratory agricultural workers in the US. The aim underpinning these projects was to move beyond the deficit discourses and stories of blame that so often circulate, particularly in relation to social groups that are marginalised, and to present stories that embody positive and productive ways of thinking and working. Using Maxwell's (2012) process of connecting, the authors used the transcripts of semi-structured interviews to construct narratives about three of the educators who were interviewed. These examples from rural education research highlighted the actions of educators to build and promote children’s and families’ relationships with the place where they were residing temporarily. The notion of querencia provided a helpful way of conceptualising the relationship between place and belonging, to assist the development of insider understandings. The narrative approach offers a way of opening such discussions in education more broadly and to consider the role of teachers in ensuring that negatively framed stories, such as deficit discourses, are not in play.